How Has the Two-Day Weekend Policy Affected Labour Supply and Household Work in China? - Tony Fang; Carl Lin; Xueli Tang (Institute of Labor Economics (IZA), 2018)
This paper examines the effects of working time reduction policy on labour supply (hours of work and whether an individual takes a second job) and household production, by exploiting the Chinese Two-Day Weekend Policy, which effectively reduced weekly working days from six to five in May 1995, as a natural experiment. We construct a theoretical model that predicts a decline in labour supply in both private and public sectors as work hours were reduced. In theory, the time spent on household production may increase or decrease or the time spent on the second job may increase or decrease depending on how much agents care about household production or the income from a second job. Using the China Health and Nutrition Survey, we adopt a difference-in-differences strategy to estimate the policy effects on work hours of wage earners in both public and private sectors. Relative to the control group deemed unaffected by the policy change, our estimates show that the Two-Day Weekend Policy significantly reduced the working hours of wage earners by 4 percent and the public sector by 5 percent while increasing the probability of having a second job by 3 percent and reducing the time spent on household work by 98-107 minutes per week. The results are robust to different specifications and a propensity score matching technique.
Keywords: J22; J28; 330; labour supply; time allocation; work hours; household production; second job; China